Enhancing Pancasila Education Learning Outcomes through the Adaptation of the CTL- Approach in Elementary Schools: A Classroom Action Research at GMIT Manumuti Tarus Elementary School - Aria Dorkas Nitbani; Andreas Ande; Adam Bol Nifu Benu (Program Studi PGSD Universitas Madako Tolitoli, 2026)
This study was conducted in response to low learning outcomes and limited student engagement in Pancasila Education, primarily due to teacher-centered instructional practices that provided few opportunities to connect learning with real-life experiences. In the pre-cycle stage, only 8 of 24 students (33.33%) achieved the minimum learning mastery criterion of 75. This study aimed to improve learning outcomes through the implementation of a Contextual Learning Approach in teaching Cultural Diversity in East Nusa Tenggara Province. A two-cycle Classroom Action Research design was employed, with each cycle consisting of planning, action, observation, and reflection. The participants were 24 fifth-grade students (12 boys and 12 girls). Data were collected through observations, learning achievement tests, and documentation. The findings revealed consistent improvement across the two cycles. Learning mastery increased from 33.33% in the pre-cycle to 41.67% in Cycle I and reached 100% in Cycle II, while the average score improved from 63.92 to 87.04. Teacher and student learning activities also increased substantially. These findings demonstrate that the CTL Approach effectively promotes student engagement, conceptual understanding, and learning outcomes. Furthermore, integrating authentic learning experiences contributes to more meaningful learning and provides a practical strategy for enhancing the quality of Pancasila Education in elementary schools.